Prevention of Aggregation and Autocatalysis for Sustaining Biological Activity of Recombinant BoNT/A-LC Upon Long-Term Storage - Singh, Padma; Kumar Singh, Manglesh; Chauhan, Vinita; Gupta, Pallavi; Kumar Dhaked, Ram (Protein and Peptide Letters, 2011)
Protein aggregation during expression, purification, storage, or transfer into requisite assay buffers hampers the use of proteins for in vitro studies. The formation of these aggregates represents a major obstacle in the study of biological activity and also restricts the spectrum of protein products being available for the biomedical applications. The catalytic light chain of botulinum neurotoxin type A undergoes autocatalysis and aggregation after purification upon long-term storage and freeze-thawing. In present study the conditions for the high level expression and purification of biologically active light chain protein of botulinum neurotoxin were optimized from a synthetic gene. Several co-solvents were screened in order to prevent autocatalysis and aggregation of rBoNT/A-LC. The effect of the co-solvents is studied on endopeptidase activity during long term storage of the recombinant protein. The purified rBoNT/A-LC was also evaluated for its immunogenicity.
Keywords: glycerol